Allele frequency of nonsense mutation responsible for hereditary nephropathy in English cocker spaniel dogs - Andrade, Larissa Rocha [UNESP]; Caceres, Amanda Manara [UNESP]; Trecenti, Anelize de Souza [UNESP]; Borges, Alexandre Secorun [UNESP]; Oliveira-Filho, Jose Paes [UNESP] (Elsevier, 2020)
Hereditary nephropathy is a primary progressive glomerular disease in dogs associated with the c.115A>T mutation in the COL4A4 gene in English cocker spaniel (ECS) dogs. The disease is inherited in an autosomal recessive manner. Hereditary nephropathy has been described in this breed since the late 1940s. To date, there are no data on the prevalence of this disease in Brazil, so the aim of this study was to evaluate the allelic frequency of this mutation in ECS dogs in this country. The DNA samples were purified from blood samples or buccal swabs from 221 ECS dogs. Fragments of the DNA containing the mutation were amplified by PCR and submitted to direct gene sequencing. The allele frequency of the mutation was 0.9%. The presence of the mutation in the ECS dog population in Brazil reveals the importance of performing the genotyping tests in these dogs as a method of diagnosing the disease and identifying heterozygous animals, aiming to reduce clinical cases of disease through mating.
Keywords: COL4A4; Diagnosis; Genetic disease; Genotyping; Hereditary nephropathy